Пошаговое объяснение:
9 - 4х = 3х - 40
-4х - 3х = -40 - 9
-7х = -49
х = -49 : (-7)
х = 7
9 - 4*7 = 3*7 - 40
9 - 28 = 21 - 40
-19 = -19
0,4(6 - 4у) = 0,5(7 - 3у) - 1,9
2,4 - 1,6у = 3,5 - 1,5у - 1,9
-1,6у + 1,5у = 3,5 - 1,9 - 2,4
-0,1у = -0,8
у = -0,8 : (-0,1)
у = 8
0,4(6 - 4*8) = 0,5(7 - 3*8) - 1,9
0,4(6 - 32) = 0,5(7 - 24) - 1,9
0,4 * (-26) = 0,5 * (-17) - 1,9
-10,4 = -8,5 - 1,9
-10,4 = -10,4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Пошаговое объяснение:
9 - 4х = 3х - 40
-4х - 3х = -40 - 9
-7х = -49
х = -49 : (-7)
х = 7
9 - 4*7 = 3*7 - 40
9 - 28 = 21 - 40
-19 = -19
0,4(6 - 4у) = 0,5(7 - 3у) - 1,9
2,4 - 1,6у = 3,5 - 1,5у - 1,9
-1,6у + 1,5у = 3,5 - 1,9 - 2,4
-0,1у = -0,8
у = -0,8 : (-0,1)
у = 8
0,4(6 - 4*8) = 0,5(7 - 3*8) - 1,9
0,4(6 - 32) = 0,5(7 - 24) - 1,9
0,4 * (-26) = 0,5 * (-17) - 1,9
-10,4 = -8,5 - 1,9
-10,4 = -10,4